Technical principles of atmospheric carbon dioxide reduction and conversion: economic considerations for some developing countries - Roduner, Emil; Rohwer, Egmont R. (Clean technologies and environmental policy, 2021)
Since natural photosynthesis in our biosphere does not have the capacity to cope with the additional atmospheric CO 2 due to combustion of fossil fuels, CO 2 has to be actively removed. Efficient methods are currently being developed, but the captured gas has to be dumped in safe and permanent storage environments. Alternatively, it has to be purified before it can be recycled catalytically, using renewable energy, to high-value chemicals as feedstock for the synthesis of polymers, fine chemicals, or in large quantities liquid solar fuels. The combustion of solar fuels is carbon-neutral. If produced at locations where renewable energy is cheap, they become an important economic opportunity. The requirement to achieve a carbon-zero energy supply also for air traffic allows planning for an as yet unknown higher price compared to that of fossil fuels. Use of solar fuels in closed cycle applications may also relieve the energy situation in the large number of off-grid households in rural Africa. The availability of energy, in particular of electricity, is essential for advanced living conditions, prevents migration to urban areas, and therefore protects a rich variation of tribal cultural, religious and social traditions. Graphic abstract